Employment Empowering Women: An Experience of Nepal - Jain, Bandana Kumari (Tribhuvan University Journal, 2020)
The study aims to examine the association between employment and the empowerment of Nepali currently married women. It harnesses women’s employment status and their empowerment; in terms of ‘household decision making’, ‘attitudes towards wife-beating’, and ownership of the house/land’ with the help of the Nepal Demographic and Health Survey (NDHS) 2016 data set. Married women’s employment exhibits a significant association (0.05) with their socio-demographic characteristics, and empowerment variables as well. The employment status of married women influences their household decision-making, and attitudes towards wife-beating. The study adheres to the belief that employment accelerates women’s empowerment, still, it is complex to determine the strength of the relationship in between. Thus, based on the findings of the study, other variables and empowerment indicators are to be considered and analyzed further for concrete insights. So, employment cannot be assumed as a mere engine and an only instrument for empowering women.